A study on flood and its impacts on community in Penampang, Sabah / Nur Sahirah Asman and Sylvianie Dominic - Asman, Nur Sahirah; Dominic, Sylvianie (2018)
This chapter is consists of 10 sections where the first section is the introduction of this chapter. The second section is the background of study where it will be briefly reviewed the area being researched. The third section consist of the problem statement, followed by the research questions of the study, objectives of the study, hypothesis of the study, scope of the study, significant of the study and the definition of key terms used in the study. In the last section will be the summary of this chapter which is located in section 10 of this chapter. This chapter will probe the readers mind by identified through problem statements.